Motor dysfunction within the schizophrenia-spectrum: A dimensional step towards an underappreciated domain - Hirjak, Dusan; Thomann, Philipp; Kubera, Katharina Maria; Wolf, Nadine D.; Sambataro, Fabio; Wolf, Robert Christian (Schizophrenia research, 2015)
At the beginning of the 20th century, genuine motor abnormalities (GMA) were considered to be intricately linked to schizophrenia. Subsequently, however, GMA have been increasingly regarded as unspecific transdiagnostic phenomena or related to side effects of antipsychotic treatment. Despite possible medication confounds, within the schizophrenia spectrum GMA have been categorized into three broad categories, i.e. neurological soft signs, abnormal involuntary movements and catatonia. Schizophrenia patients show a substantial overlap across a broad range of distinct motor signs and symptoms suggesting a prominent involvement of the motor system in disease pathophysiology. There have been several attempts to increase reliability and validity in diagnosing schizophrenia based on behavior and neurobiology, yet relatively little attention has been paid to the motor domain in the past. Nevertheless, accumulating neuroscientific evidence suggests the possibility of a motor endophenotype in schizophrenia, and that GMA could represent a specific dimension within the schizophrenia-spectrum. Here, we review current neuroimaging research on GMA in schizophrenia with an emphasis on distinct and common mechanisms of brain dysfunction. Based on a dimensional approach we show that multimodal neuroimaging combined with fine-grained clinical examination can result in a comprehensive characterization of structural and functional brain changes that are presumed to underlie core GMA in schizophrenia. We discuss the possibility of a distinct motor domain, together with its implications for future research. Investigating GMA by means of multimodal neuroimaging can essentially contribute at identifying novel and biologically reliable phenotypes in psychiatry.
Gesehen am 03.09.2020